The hard and soft of health care - Wayne Willis, R. (Journal of religion and health, 1995)
For several decades, the American system of health care delivery has trusted scientific modalities to bring healing. This article points out the limitations of scientific medicine, the timelessness of spiritual components of healing, and the ongoing need for hospital personnel who are sensitive to the healing properties of faith, hope, and love.